Production economics and resource use efficiency of tomato under open field condition in Kapilvastu, Nepal - Subedi, Manoj; Pandey, Madhav; Ojha, Rakesh Kumar; Acharya, Bibek (Journal of Agriculture and Natural Resources, 2020)
A study was conducted in Kapilvastu district with an objective to analyze the production economics and resource use efficiency of tomato production under open field condition. Altogether ninety tomato growers were purposely selected for household survey. Primary data were collected using pre-tested interviews and focus group discussion with tomato farmers and stakeholders. Data was analyzed using SPSS and STATA, and socio-demographic characteristics, Cobb-Douglas production function and resource use efficiency of the tomato farmers was studied. The tomato production in the studied site was found to be a labor-intensive venture as cost incurred for labor was about 39 percent of the total cost with gross margin of NRs. 7255.10 per kattha and net profit of NRs. 5464.1 per kattha. Cobb-Douglas production function analysis showed positive and significant relationship of cost on labor, seed, farm yard manure, inorganic fertilizer and micronutrients and other associated expenses with the gross income. The returns to scale of 1.02 indicated increasing returns to scale whereas resource use efficiency values indicated all input resources were underutilized in tomato production.